A Glance at the Nuclear Envelope Spectrin Repeat Protein 3 - Liao, Liwei; Qu, Rongmei; Ouang, Jun; Dai, Jingxing (BioMed Research International, 2019)
Nuclear envelope spectrin repeat protein 3 (nesprin-3) is an evolutionarily-conserved structural protein, widely-expressed in vertebrate cells. Along with other nesprin family members, nesprin-3 acts as an essential component of the linker of nucleoskeleton and cytoskeleton (LINC) complex. Naturally, nesprin-3 shares many functions with LINC, including the localization of various cellular structures and bridging of the nucleoskeleton and cytoskeleton, observed in vitro. When nesprin-3 was knocked down in vivo, using zebrafish and mouse models, however, the animals were minimally affected. This paradoxical observation should not limit the physiological importance of nesprin-3, as recently, nesprin-3 has reignited the interest of the research community in studies on cancer cells migration. Moreover, nesprin-3 also plays an active role in certain developmental conditions such as adipogenesis and spermatogenesis, although more studies are needed. Meanwhile, the various protein binding partners of nesprin-3 should also be emphasized, as they are necessary for maintaining the structure of nesprin-3 and enabling it to carry out its various physiological and pathological functions. Nesprin-3 promises to further our understanding of these complex cellular events. Therefore, this review will focus on nesprin-3, examining it from a genetic, structural, and functional perspective. The final part of the review will in turn address the limitations of existing research and the future perspectives for the study of nesprin-3.